Concentración de metales pesados mercurio y plomo en concha prieta (Anadara tuberculosa) del refugio de vida silvestre Isla Corazón y Fragatas - Santana Zambrano, María De Los Ángeles (2022)
The purpose of this research was to determine the concentration level of mercury and lead in Concha Prieta (Anadara tuberculosa) at Isla Corazón y Fragatas wildlife refuge. The selected area was Isla del Sol, where species with the size allowed for their capture were found. The levels of mercury and lead in the soft tissue were determined using the ICP-OES technique and the Pearson coefficient was applied between the physical parameters of the water and sediment vs. the concentrations of heavy metals. As a result, it was found that the average concentrations of Hg (M1= 0.006 mg/kg, M2= 0.017 mg/kg and M3= 0.023 mg/kg) and Pb (M1= 1.0567 mg/kg, M2= N/D mg /kg and M3= 0.535 mg/kg) did not exceed the maximum permissible ranges according to European Regulations (0.5 mg/kg) and (1.5 mg/kg). In addition, the physicochemical parameters of the water and sediment evaluated did not exceed the criteria contemplated, observing that there are no consequences between these and the values of Hg and Pb. It follows that the concentrations of mercury and lead quantified in this species of bivalve mollusk do not generate an impact on biodiversity in the protected area.